Fortune and glory : [large type] tantalizing twenty-seven - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 2020)
When Stephanie's beloved Grandma Mazur's new husband died on their wedding night, the only thing he left her was a beat-up old easy chair... and the keys to a life-changing fortune. But as Stephanie and Grandma Mazur search for Jimmy Rosolli's treasure, two dangerous enemies from the past stand in their way--along with a formidable new adversary. Gabriela Rose, a dark-eyed beauty from Little Havana with a taste for designer clothes. She's also a soldier of fortune, a gourmet cook, an expert in firearms and mixed martial arts. Stephanie may be in over her head, but she's got a stubborn streak that will never let her quit.